The Influence of Halal Labeling and Product Quality on Intention to Purchase Azarina Hydrasoothe Sunscreen - Rini, Ika Tirta Candra; Hartadi, Agung; Budiningrum, Endah Wening (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2024)
This  study aims to determine the effect of halal labeling and product quality on buying intention of Azarine Hydrosoothe Sunscreen. This research approach uses quantitative research .The research was conducted in March. The number samples in the study were 109 respondents using the accidental sampling technique. Then analyse the data obtained in the from of quantitativ e analysis which includes descrptive analysis, validity test, reliability test, hypothesis testing  through t test. Test the analysis of the coefficient  of  determinan (R2) classical assumption test and multiple linier regression analysis  which serves to see the influence between variables. The results of this study indicate that halal labeling  and product quality have an effect on purchas intention. Correlation coefficeient  (R) value is 0,830  which indicates a strong and positifve relationship. While the coefficient  of determinan   (adjusted R2) is 0, 682. This  shows that 0,682 or 68,2% of purchase intention is influenced by the independet variables, namely halal labeling and product quality, while the remaining 31,8% is influenced by order variables not examined in this study